High Rise Building Evacuation Route Model Using DIJKSTRA'S Algorithm - Mohd Sabri, Nor Amalina (2015)
Evacuation of high rise building has become an issue nowadays as the modern development has increased tremendously with a very complex structure and design. The complexity and height of the building can affect the successfulness of the evacuation process, especially towards unfamiliar occupants in the building. Generally, they only know the route taken while they enter the building. Moreover, the available evacuation map provided by the building is not showing the shortest and safest path. Subsequently, they are hard to find the optimal route to escape. Furthermore, the shortest path algorithm needed additional features to produce better result. This research aims to assist the evacuees to find the shortest path in a high rise building using a shortest path algorithm. The objective is to design and develop an evacuation route using shortest path algorithm based on the evacuation map of the building. The method involves in this research starts with abstracting the original floor plan of the high rise building into CAD format. The floor plan is an important data to be used in this study, which is to design the evacuation route of the building. However, the original floor plan is visualised into 2D layout to gather the information on nodes and weights. The information then is used to generate a directed graph in order to obtain the shortest path results through the implementation of shortest path algorithm. The main algorithms involve is Dijkstra’s algorithm and then an Ant Colony Optimization algorithm is used as hybrid versions of Dijkstra’s algorithm. As a result, the evacuation route model is able to gain the shortest path and safest path consistently between Dijkstra’s algorithms and hybrid version which is Dijkstra-Ant Colony Optimization (DACO). In conclusion, based on the results, the shortest path can be implemented into a computerized evacuation map of the high rise building which can assist evacuees in pre evacuation to find the shortest and safest path to evacuate.